Voto: uma oferta de fé. O poder simbólico dos líderes religiosos e o comportamento eleitoral dos membros da igreja evangélica - Souza, Julio Cesar Pereira de (2011)
The way of making politics in the churches in Brazil has changed considerably due to the growth of evangelical denominations. The neopentecostal churches , emerged in the mid-70s, grew up quickly and now they are communities strongly disputed by the political leadership to represent an important portion of the national constituency. Considering the problem of charisma, the symbolic capital, i.e, the influence of the religious leader, we studied the voting behavior of campaigns for state and federal deputies in the International Church of God`s Grace (Igreja Internacional da Graça de Deus) from 1998 to 2006 addressing the transformation of its members in militants and faithful voters. Therefore, we analyze the guidelines of the speech delivered by the church leadership in the process of electoral persuasion, the media material, the logistics of the campaign and the participation of members in this process.